Family Food Availability Income and Consumption Patterns Cause Wasting in Toddlers in Martapura Timur District - Abdurrachim, Rijanti; Nurhamidi, Nurhamidi; Hariati, Niken Widiastuti; Anwar, Rosihan; Emelia, Herizka Rizti (International Journal of Public Health Excellence (IJPHE), 2025)
Asting, a condition characterized by low body weight in toddlers, has a prevalence of 28.94% in Martapura Timur District. This study aimed to explore the relationship between income, food availability, and consumption patterns as factors contributing to wasting among toddlers aged 12-59 months. Using a Cross-Sectional design, data were collected from 45 purposively sampled toddlers through questionnaires, food availability forms, and food frequency forms. Spearman Rank correlation (α=0.05) was employed for data analysis. Findings revealed that most mothers were under 20 or over 35 years old, with junior high school education and predominantly unemployed. Male toddlers were slightly more prevalent, with 82.2% classified as wasting and 17.8% in severe wasting. Low family income (below the minimum wage) was common (71.1%), and food availability ranged from insufficient to barely sufficient. Consumption patterns were largely suboptimal (64.4%), with staple food intake (<150 g/day) limited to rice and corn, animal protein (50 g/day) from eggs only, plant protein (<40 g/day) primarily from tofu, and minimum vegetable consumption (30 g/week of pumpkin, 1-3 times weekly). Statistical analysis indicated significant relationships between family income (p=0.048, r=0.296), food availability (p=0.048, r=0.296), and consumption patterns (ρ=0.002, r=0.455) with wasting. The strongest relationship was found in food availability. Efforts are being made to increase awareness through health centers, encouraging mothers to utilize home yards for food production, enhancing food availability, and improving children's diets. Addressing these factors can help reduce the prevalence of wasting and promote better nutrition in toddlers.